Comparative in vitro activities of LY191145, a new glycopeptide, and vancomycin against Staphylococcus aureus and Staphylococcus-infected fibrin clots. - Kang, S L (1995)
Bactericidal activities of LY191145, an investigational glycopeptide, and vancomycin against Staphylococcus aureus were evaluated. Only LY191145 at a concentration 16-fold greater than the MIC was able to achieve 99.9% killing against methicillin-susceptible S. aureus (ATCC 25923; 8.0 h). Both agents demonstrated 99.9% killing against methicillin-resistant clinical isolate S. aureus MRSA67 over 24 h at concentrations 4-, 8-, and 16-fold greater than the MIC, but bacteria were killed at a more rapid rate by LY191145 (1.63 versus 5.02 h; P < 0.001). Against strain ATCC 25923- and MRSA67-infected fibrin clots, total reductions by LY191145 and vancomycin over 72 h were not statistically significantly different at a concentration 16 times the MIC (1.12 +/- 0.31 and 1.23 +/- 0.13 and 1.40 +/- 0.17 and 1.36 +/- 0.37 CFU/g; respectively). Increasing the drug concentration to 50 times the MIC did not alter the values significantly, and there was no statistically significant difference between the two agents. Overall, LY191145 exhibited more rapid bactericidal activity than vancomycin against S. aureus, and a concentration 16-fold greater than the MIC appears to be optimal.